The Implementation of Pulse-Density Modulated Wireless Power System Using a Sliding Mode Controller - Prosen, Nataša; Truntič, Mitja; Mihalič, Franc; Domajnko, Jure (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The efficiency of the wireless power transfer (WPT) using a half-bridge inverter on the transmitter side can be increased by switching from frequency modulation (FM) to pulse density modulation (PDM). The method of generating PDM, described and implemented in this paper is based on a sliding mode controller (SMC), which also serves as a transmitter coil current controller. The current controller is in a cascade with the output voltage controller, which can be implemented either on the transmitter or on the receiver side.